Pola-Pola Interpretasi Permainan Higgs Domino Terhadap Remaja - Saiful Azwar; Wahida Wahyuni; Kurniadi Ilham (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The work POLA-POLA was inspired by the online game Higgs Domino where the creator was interested in the algorithmic patterns of the game. This game is not only played by teenagers but is also played by children and even the elderly. This game has its own uniqueness, namely that there are boxes where the spin moves from top to bottom so that wins and losses appear in the box. The artist interpreted these boxes in the work POLA-POLA by using six cubes of different sizes and each side has a different color, consisting of red, yellow, green and white. In creating the dance work entitled POLA-OLA, the methods of observation, exploration, improvisation and formation were used. Supporting the work consists of six dancers, namely three male dancers and three female dancers. The POLA-POLA dance work was performed at the Hoerijah Adam Performance Building, Padangpanjang Indonesian Arts Institute. This dance work is presented in the form of a contemporary dance work.